Challenges and Opportunities for Sustaining Purposeful Professional Collaboration: Leadership Frames in Urban Schools Under Pressure to Improve. Issue 4 (2nd October 2022) - Weddle, Hayley
ABSTRACT: A better understanding of the ways in which school leaders frame collaboration is needed, as the framing of reform efforts plays a large role in steering change. This study explores how leaders' frames for collaboration intersect with teachers' collaborative work in four urban middle schools over time. Findings demonstrate the role of accountability pressures in shaping leadership frames about the purpose of collaboration, and misalignment between these frames and qualities of purposeful collaboration. Findings also illustrate a dynamic relationship between leadership frames and teacher collaboration. Ultimately, fostering effective collaborative cultures remained challenging even in schools with increasingly teacher-led collaboration.